Youth comedy vs. social drama: the origins of Sergei Gerasimov's system for training filmmakers. (4th May 2019) - Sputnitskaia, Nina
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this article is dedicated to the first period of Sergei Gerasimov's directorial work, when he laid the foundations of his pedagogical system. It introduces previously unexplored and unpublished archival materials to academic discourse. Gerasimov's fiction films, particularly The New Teacher (1939) and Masquerade (1941), are the centre of attention. During their production the director's style and method were shaped and his work with literary and dramatic material defined. The article explores how the method of the director's work with the actor emerged and developed. Special attention is paid to the structure of female images in Gerasimov's first directorial works, beginning with the comedy Do I Love You? (1934), which has not been preserved. Female characters are key in the creative work and the subsequent films of the director. The analysis of the early period of Gerasimov's directorial work (the pre-war period) allows us to draw conclusions about the formation of an idiosyncratic conception of the director.